2019
DOI: 10.1177/0972150919845220
|View full text |Cite
|
Sign up to set email alerts
|

Propping in Business Groups: Prediction Efficacy of Earnings Announcements

Abstract: This study examines the evidences of propping in business groups in India. The article is an empirical study which adopts the event study method to ascertain the price reaction to the earnings announcement by listed group firms. Results indicate that the earnings announcements are perceived to have a positive effect on the financial health of other firms of the group. The cumulative abnormal return (CAR) of the portfolio of nonannouncing firms in a business group is found to be strongly and positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The RPT is more likely to be driven by transaction cost issues than by private opportunities issues. Study in India through an event approach found evidence of propping in business groups in India (Maheshwari & Gupta, 2019). The results of the study found that earnings announcements have a positive effect on the financial health of other companies in the business group.…”
Section: Related Loans As An Efficient Transactionsmentioning
confidence: 85%
“…The RPT is more likely to be driven by transaction cost issues than by private opportunities issues. Study in India through an event approach found evidence of propping in business groups in India (Maheshwari & Gupta, 2019). The results of the study found that earnings announcements have a positive effect on the financial health of other companies in the business group.…”
Section: Related Loans As An Efficient Transactionsmentioning
confidence: 85%